“Transformational Ministry” and “Reparative Therapy:” Transformative Learning Gone Awry - Andre P. Grace (Adult Education Research Conference, 2002)
This essay interrogates how “reparative therapy” and “transformational ministry” debase queer. It takes up Cornell West’s notion of radical pedagogy to explore possibilities for a politics and pedagogy conducive to radical, democratic transformative learning. It provides an overview of my cultural work to advocate for queer persons.